Kebijakan Dividen Terhadap Nilai Perusahaan Listed BEI 2018-2022: Peran Moderasi Struktur Modal, Size, Profitabilitas - Indro Purnomo; Hwihanus (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to examine the effect of dividend policy on company value and examine the effect of dividend policy on company value which is moderated by capital structure, company size and profitability. The population of this research is hotels, restaurants and tourism sub-sector companies listed on the IDX with a research period of 2018-2022. The number of samples is 4 companies with total data of 20 observations. The data source uses secondary data, namely in the form of company annual reports which can be accessed via the website www.idx.co.id. The data analysis technique uses SEM PLS analysis, with the help of Smart-PLS version 3. Conclusions from this research (1) Dividend policy has a positive and significant effect on company value in hotel, restaurant and tourism sub-sector companies listed on the BEI for the 2018-2022 period. (2) Capital structure cannot moderate the influence of dividend policy on company value. (3) Company size cannot moderate the influence of dividend policy on company value (4) Profitability cannot moderate the influence of dividend policy on company value.